2022
DOI: 10.3389/fgene.2022.804584
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis for Resistance Against Viral Nervous Necrosis: GWAS and Potential of Genomic Prediction Explored in Farmed European Sea Bass (Dicentrarchus labrax)

Abstract: Viral nervous necrosis (VNN) is an infectious disease caused by the red-spotted grouper nervous necrosis virus (RGNNV) in European sea bass and is considered a serious concern for the aquaculture industry with fry and juveniles being highly susceptible. To understand the genetic basis for resistance against VNN, a survival phenotype through the challenge test against the RGNNV was recorded in populations from multiple year classes (YC2016 and YC2017). A total of 4,851 individuals from 181 families were tested,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 55 publications
3
16
2
Order By: Relevance
“…Our results show that heritability estimates for VNN survival using imputed genotypes (0.21-0.22 on the observed scale) are of the same magnitude as values obtained in previous studies on NNV-infected sea bass, 0.08 to 0.23 on the observed scale in [10,23] and 0.15 to 0.43 on the liability scale in [18,39]. The number of breeders used to obtain challenged individuals as well as the number of experimental individuals, the method of infection during viral challenges, the age and size at challenge and the genetic origin and/or the experimental design are parameters that may explain the differences between the estimates of NNV survival in these studies [39].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our results show that heritability estimates for VNN survival using imputed genotypes (0.21-0.22 on the observed scale) are of the same magnitude as values obtained in previous studies on NNV-infected sea bass, 0.08 to 0.23 on the observed scale in [10,23] and 0.15 to 0.43 on the liability scale in [18,39]. The number of breeders used to obtain challenged individuals as well as the number of experimental individuals, the method of infection during viral challenges, the age and size at challenge and the genetic origin and/or the experimental design are parameters that may explain the differences between the estimates of NNV survival in these studies [39].…”
Section: Discussionsupporting
confidence: 85%
“…None of these genes have been previously reported in the literature in view of association studies for survival to VNN. Interestingly, LG12_QTL_2 and these two genes are located more than 2.5 Mb away from the QTL region identified by Vela-Avitúa et al [23] and where the HSP70 gene is located, which was also reported in a transcriptomic analysis of response to VNN in Asian sea bass [41]. This may be a consequence of the much higher precision of our localisation, as the LG12_QTL_2 region is only 127 kb, while the region identified in [22] is 7 Mb wide.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations